Bibliometric Analysis Of The Development Of Digital Systems, Applications, And Products In Data Processing (SAP) During The 2018–2024 Period - Nadia Fahima; Gugus Irianto (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to map the development of research on Systems, Applications, and Products in Data Processing (SAP) during the 2018–2024 period using a bibliometric approach. Research data were collected from the Scopus database through a literature selection process based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, resulting in 316 publications that met the inclusion criteria. Publication metadata were analyzed using VOSviewer through co-occurrence, overlay visualization, density visualization, and co-authorship network analyses to identify publication trends, thematic developments, and scientific collaboration patterns. The findings indicate that SAP-related publications remained relatively stable with moderate fluctuations, increasing from 42 publications in 2018 to a peak of 53 publications in 2022. The keyword network structure highlights SAP, Enterprise Resource Planning (ERP), and enterprise systems as core themes interconnected with digital transformation, cloud computing, process mining, artificial intelligence, machine learning, and SAP S/4HANA. Temporal analysis reveals a shift in research focus from conventional ERP implementation toward the development of enterprise systems increasingly integrated with digital technologies and data-driven capabilities. Furthermore, the co-authorship analysis demonstrates the emergence of international collaboration networks involving researchers from various countries in advancing SAP-related studies. Overall, the results provide a comprehensive overview of the evolution of SAP research and identify promising directions for future studies in the era of digital transformation.